Information literacy and the educational, technological, political and organizational contexts - Capinzaiki Ottonicar, Selma Leticia [UNESP]; Pomim Valentim, Marta Ligia [UNESP]; Feres, Gloria Georges [UNESP] (Univ Brasilia, Dept Ciencia Informacao, 2016)
Nowadays Information Literacy is studied in different contexts in society. So an article which demonstrates the main influences of this literacy contributes to the construction of researcher and general pubic complex thought. This paper has the following research problem: how does information literacy influences in the different social contexts? There were chosen the main influence to provide an amplified vision about the subject however; a research that show not all perspectives of a knowledge is possible. As methodological procedures, this article introduces an investigative research based on a literature review. As a final consideration, information literacy is present in policy, since it is a factor that allows exercise of citizenship; it is also present at schools developing students' learning. In addition, it is necessary to use technology and it is a strategy for competitiveness in organizations.
Keywords: information literacy; interdisciplinary; complex thought; information literacy contexts